Antimicrobial activity of four plants from Peruvian north-east - Ruiz Q., Julio R. (2009)
The present work investigated the in vitro antimicrobial activities of ethanolic, methonolic and hydroalcoholic extracts corresponding to four plants of north easter of Peru; Cassia reticulata (whole plant), Ilex guayusa Loes (leaves), Piper lineatum (leaves), y Terminalia catappa (leaves). The plants were collected in the department of Cajamarca, except Terminalia catappa (Amazonas). The antimicrobial activity was determinated by the method of agar diffusion. The used microorganisms were the bacteria Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, Bacillus subtilis and Escherichia coli; and the fungals Candida albicans, Aspergillus niger and Microsporum canis. Of twelve investigated extracts, eight (67%) presented significant antimicrobial activity against Staphylococcus aureus and Staphylococcus epidermidis and one (8%) against Escherichia coli. Of twelve investigated extracts, ten (83%) presented significant activity against Candida albicans, and six (50%) against Microsporum canis. The extracts with the greatest antimicrobial activity were the three extracts of Piper lineatum, the hydroalcoholic extract of Cassia reticulata and the hydroalcoholic extract of Terminalia catappa.